Fine-tuning the BFOLDS Fire Regime Module to support the assessment of fire-related functions and services in a changing Mediterranean mountain landscape. (September 2022) - Sil, Ângelo; Azevedo, João C.; Fernandes, Paulo M.; Alonso, Joaquim; Honrado, João P.
Abstract: Fire simulation models are useful to advance fire research and improve landscape management. However, a better understanding of these tools is crucial to increase their reliability and expansion into research fields where their application remains limited (e.g., ecosystem services). We evaluated several components of the BFOLDS Fire Regime Module and then tested its ability to simulate fire regime attributes in a Mediterranean mountainous landscape. Based on model outputs, we assessed the landscape fire regulation capacity over time and its implications for supporting the climate regulation ecosystem service. We found that input data quality and the adjustment of fuel and fire behaviour parameters are crucial to accurately emulating key fire regime attributes. Besides, the high predictive capacity shown by BFOLDS-FRM allows to reliably inform the planning and sustainable management of fire-prone mountainous areas of the Mediterranean. Moreover, we identified and discussed modelling limitations and made recommendations to improve future model applications. Highlights: Model evaluation supports the application of BFOLDS-FRM to Mediterranean landscapes. The model adequately emulates key fire regime attributes in mountain landscapes. Model outputs allow estimation of fire- and climate-related functions and services. BFOLDS-FRM can support fire-smart management of Mediterranean mountain landscapes.